Sistem Informasi Consultation Online Menggunakan Bahasa Pemograman PHP dan Database MySQL - Yuspita, Yulifda Elin (Mahesa Research Institute, 2023)
This research focuses on the description of the current system to determine the problems that occur and the system requirements needed. Then from the analysis, a global design is made which aims to provide a general description to the user about the new system and identify the components of the information system that will be designed in detail. The design includes display design, output design, input design, and file design. In the end, an online construction consultant consultation application was made and then the new system was tested, so that it could overcome the problems encountered in the old system. So it can be concluded that the application of the online construction consultant consultation application will make it easier for clients to consult directly if the consultant is out of town without having to wait and make an appointment with the consultant first.